Cystathione gamma lyase/Hydrogen Sulphide Pathway Up Regulation Enhances the Responsiveness of α1A and α1B-Adrenoreceptors in the Kidney of Rats with Left Ventricular Hypertrophy - Ahmad, A.; Sattar, M.A.; Azam, M.; Abdulla, M.H.; Khan, S.A.; Hashmi, F.; Abdullah, N.A.; Johns, E.J. (Public Library of Science, 2016)
The purpose of the present study was to investigate the interaction between H2S and NO (nitric oxide) in the kidney and to evaluate its impact on the functional contribution of α1A and α1B-adrenoreceptors subtypes mediating the renal vasoconstriction in the kidney of rats with left ventricular hypertrophy (LVH). In rats the LVH induction was by isoprenaline administration and caffeine in the drinking water together with intraperitoneal administration of H2S. The responsiveness of α1A and α1B to exogenous noradrenaline, phenylephrine and methoxaminein the absence and presence of 5-methylurapidil (5-MeU) and chloroethylclonidine (CEC) was studied. Cystathione gamma lyase (CSE), cystathione β synthase (CBS), 3-mercaptopyruvate sulphar transferase (3-MST) and endothelial nitric oxide synthase (eNOS) were quantified. There was significant up regulation of CSE and eNOS in the LVH-H2S compared to the LVH group (P<0.05). Baseline renal cortical blood perfusion (RCBP) was increased (P<0.05) in the LVH-H2S compared to the LVH group. The responsiveness of α1A-adrenergic receptors to adrenergic agonists was increased (P<0.05) after administration of low dose 5-Methylurapidil in the LVH-H2S group while α1B-adrenergic receptors responsiveness to adrenergic agonists were increased (P<0.05) by both low and high dose chloroethylclonidine in the LVH-H2S group. Treatment of LVH with H2S resulted in up-regulation of CSE/H2S, CBS, and 3-MST and eNOS/NO/cGMP pathways in the kidney. These up regulation of CSE/H2S, CBS, and 3-MST and eNOS/NO/cGMP pathways enhanced the responsiveness of α1A and α1B-adrenoreceptors subtypes to adrenergic agonists in LVH-H2S. These findings indicate an important role for H2S in modulating deranged signalling in the renal vasculature resulting from LVH development.